Akram Khan, Lloyd Newson, and the Challenges of British Multiculturalism. (November 2018) - Kolb, Alexandra
Abstract : In a climate riven by national insecurities, anti-immigration movements and competing visions of a post-Brexit future, this paper examines the contentious space multiculturalism has inhabited in 21 st -century British choreography. It analyses acclaimed works by Akram Khan and Lloyd Newson to explore starkly differing perspectives on cultural diversity in the UK. Khan's contribution to the London 2012 Olympics Opening Ceremony (Abide with Me) emphasised the nation's post-imperialist and cosmopolitan profile. By contrast, Newson's contemporaneous work Can We Talk about this? (2011/12) was highly critical of current models of multiculturalism and in particular attitudes towards Islam. This paper compares the two choreographies using a theoretical framework that draws on both political thought and dance analysis, to evaluate their contributions to debates around culture, tolerance and diasporic identities and illustrate the broader entanglement between British dance and contemporary politics.